Experimental and theoretical studies of reinforced concrete structures using fine aggregates from iron ore beneficiation waste - Valovoi , Oleksandr; Brovko, Dmytro; Valovoi, Maksym; Popruha, Dmytro; Eremenko, Alexander (Academic journal Industrial Machine Building Civil Engineering, 2024)
Beneficiation waste from mining and processing plants possesses the characteristics of strong and inexpensive aggregates suitable for structural reinforced concrete. This enables the practical use of such waste in the production of precast reinforced concrete. Practice has demonstrated the feasibility of using iron ore beneficiation waste as fine aggregate in concrete. The authors conducted studies on the behavior of concrete structures incorporating fine aggregates derived from iron ore beneficiation waste. This article presents the results of research on concrete, elements, and structures with fine aggregates from iron ore beneficiation waste under low-cycle loading.